Commodity price variability monthly summary - May 2023 - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
About the Excessive Food Price Variability Tool The Excessive Food Price Variability Early Warning System was developed and is maintained by IFPRl's Food Security Portal (FSP). It identifies periods of unusual price variability in world commodity markets (i.e. price variability that exceeds a pre-established estimated band). It is updated daily and uses a traffic light system that alerts about the number of days of high, moderate, or low price variability. The excessive price variability measures are estimated through a model of the day to day fluctuations of price variations in futures commodity markets. For all data, trends, and methods, see: https://www.foodsecurityportal.org